AVALIAÇÃO DE UM TREINAMENTO EM HABILIDADES SOCIAIS PROFISSIONAIS EM ENFERMEIROS GESTORES - SIQUEIRA, Morganna Ferreira de (2024)
Nursing professionals are increasingly occupying management positions in healthcare units and find themselves in environments that require high levels of social competence, which are essential both for maintaining healthy relationships and for achieving organizational goals. The aim of this study was to evaluate a Social Skills Training (SST) course for nurses who held leadership positions in hospital units on their repertoire of social and professional skills, to identify the participants' repertoire of social skills before and after the intervention and to evaluate the participants' feedback on the teaching procedures. To this end, an experimental study was conducted in which 14 nurse managers were randomly divided into an experimental and control group. The training was carried out online, with seven weekly sessions lasting 90 minutes each using the Google Meet platform. The measuring instruments were the Social Skills Inventory (IHS-II) and the Manager's Self-Perception Questionnaire. The results showed that there was no significant difference between the medians of the pre- and post-tests of the experimental and control groups, nor between the experimental and control groups. The feedback from the participants points to the positive impact of the THS on their day-to-day work, especially in terms of decision-making processes and also how problems in the work environment and lack of time can impact on the effectiveness of the training. The results point to the need for social skills training to assess the relationship between the time available for training and the amount of content to be taught.